Developing a single-session strategy for the implementation of take-home naloxone by community pharmacists using COM-B and design-thinking - Moullin, Joanna; Ely, Philip; Uren, Hannah; Staniland, Lexy; Nielsen, Suzanne; Lenton, Simon (Frontiers Media, 2023)
Background: Despite the overwhelming evidence of its effectiveness, there is poor implementation of take-home naloxone by pharmacists. Barriers have been explored and mapped to the capability, opportunity, motivation—behaviour (COM-B) model of behaviour change, yet no theoretically informed implementation strategies that target known barriers have been developed. Single-session implementation strategies have been proposed as a simple, scalable way to target multiple barriers.